Influence of mode and design factors on the temperature condition of automobile drum brakes - Hustav Hudz; Mykhailo Hlobchak (Transport Technologies)
The current state of the highway pavement makes it possible to implement prompt transportation operations. These circumstances lead to the movement of vehicles at high speeds, which is impossible without a braking system capable of ensuring high braking efficiency and optimal flow of the process from the standpoint of stability and controllability.